The Prerequisites for the Formation of Delimitation of Competence Between Russian Federation and It’s Regionsin Realization of the Social Security - Anna V. Trutaeva (Сибирское юридическое обозрение, 2017)
The article considers the settings for forming a delimitation of competence between Russian Federation and its regions in the field of social security. The Author makes a conclusion about the historical preconditions of the conception of legal regulation in the sphere of social security.